Loss of hnRNPA2B1 inhibits malignant capability and promotes apoptosis via down-regulating Lin28B expression in ovarian cancer. (10th April 2020) - Yang, Yu; Wei, Qinglv; Tang, Yuling; Yuanyuan Wang,; Luo, Qingya; Zhao, Hongyan; He, Min; Wang, Haocheng; Zeng, Qi; Lu, Weiliang; Xu, Jing; Liu, Tao; et al.
Abstract: Ovarian cancer has the highest mortality rate among all gynecological cancers with its pathogenic mechanisms largely unknown. Here, we uncovered that ovarian cancer tissues exhibit higher heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1) expression than normal ovarian epithelium tissues. Increased hnRNPA2B1 level matches along with poor prognosis of ovarian cancer patients. Importantly, hnRNPA2B1 inhibition hampers growth, reduces mobility of ovarian cancer cells in vitro and hinders xenograft tumor formation in vivo . Transcriptome profiling analysis reveals that hnRNPA2B1 dictates the expression of various important genes involved in tumorigenesis and Lin-28 Homolog B (Lin28B) is down-regulated upon hnRNPA2B1 loss. hnRNPA2B1 regulates expression of Lin28B via binding to Lin28B mRNA and enhancing its stability. Furthermore, knockdown of Lin28B reduces proliferation and mobility of ovarian cancer cells and impairs tumorigenesis in vivo, whereas Lin28B overexpression promotes xenograft tumor formation. Finally, re-expression of Lin28B in hnRNPA2B1 knockdown cells results in rescued phenotypes. Collectively, our results demonstrate that hnRNPA2B1 facilitates the malignant phenotype of ovarian cancer through activating Lin28B expression. Highlights: Loss of hnRNPA2B1 inhibits ovarian cancer progression. hnRNPA2B1 regulates expression of Lin28B via enhancing its mRNA stability. Lin28B facilitates tumorigenesis in ovarian cancer. hnRNPA2B1-Lin28B axis is critical for the progression of ovarian cancer.